Genetic homogeneity in the seagrass Cymodocea nodosa at its northern Atlantic limit revealed through RAPD - Alberto, Filipe (2018)
Random amplified polymorphic DNA (RAPD) markers were used to analyse the genetic variability of the dioecious seagrass Cymodocea nodosa Ucria (Ascherson) in the Ria Formosa lagoon, Portugal, the species' northern limit in the Atlantic. Three individuals from each of 6 meadows were genotyped with 28 primers. Meadows described previously as having flower marks were compared with meadows where flowers did not occur. A single polymorphic band, specific for one meadow, was observed in a total of 177 fragments. The lack of genetic variability among meadows both with and without flower indicates that flower production is not associated with a higher level of genetic variation. The genetic homogeneity of C, nodosa in the Ria Formosa suggests a founder effect, produced by a single or a limited number of migrants composing the colonising gene pool, This hypothesis is supported by the geographic isolation from other populations as the nearest populations lie more than 300 km away from the Ria Formosa. The lack of reproductive success of C, nodosa in Ria Formosa natural park and its low genetic variability are important factors in the conservation of this species since recolonisation can only occur through vegetative growth.